Shoe Bending Stiffness Influence on Lower Extremity Energetics in Consecutive Jump Take-Off - Sheng-Wei Jia; Fan Yang; Yi Wang; Tongtong Guo; Wing-Kai Lam (Applied Bionics and Biomechanics)
Objective. This study examined the influence of shoe bending stiffness on lower extremity energetics in the take-off phase of consecutive jump. Methods. Fifteen basketball and volleyball players wearing control shoes and stiff shoes performed consecutive jumps. Joint angle, angular velocity, moments, power, jump height, take-off velocity, take-off time, and peak vertical ground reaction force data were simultaneously captured by motion capture system and force platform. Paired t-tests were performed on data for the two shoe conditions that fit the normal distribution assumptions, otherwise Wilcoxon signed-rank tests. Results. There are significant differences (P<0.05) in take-off velocity and take-off time between stiff and control shoe conditions; the stiff shoes had faster take-off velocity and shorter take-off time than control shoes. There was no significant difference between two conditions in jump height (P=0.512) and peak vertical ground reaction force (P=0.589). The stiff shoes had significantly lower MTP dorsiflexion angle and greater joint work than the control shoes (P<0.05). The MTP range of motion and maximum angular velocity in stiff shoe condition were significantly lower than those in control shoe condition (P<0.01). However, there are no significant differences between two conditions in kinetics and kinematics of the ankle, knee, and hip joint. Conclusions. The findings suggest that wearing stiff shoes can reduce the effect of participation of the MTP joint at work and optimize the energy structure of lower-limb movement during consecutive jumps.